2011
DOI: 10.1136/annrheumdis-2011-200343
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between joint damage and functional disability in rheumatoid arthritis: a systematic review

Abstract: While many of the studies did not include multivariate analysis with confounder adjustment, the published evidence indicates a link between joint damage and functional disability and that an increase in joint damage is associated with an increase in disability over time. Treatments to limit progressive joint damage may lead to better joint function and improved patient outcome with less disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
2
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 56 publications
4
55
2
5
Order By: Relevance
“…Physical disability, here assessed by the HAQ, may in RA be associated with the unbalanced body composition per se (29) or be a consequence of both inflammatory activity and joint damage (30). With increasing disease duration, however, there is a link between joint damage and functional disability (31). Therefore, we cannot exclude that in the patients in the present study, obesity, which was associated with a higher HAQ score, was associated with increased joint destruction.…”
Section: Discussioncontrasting
confidence: 48%
“…Physical disability, here assessed by the HAQ, may in RA be associated with the unbalanced body composition per se (29) or be a consequence of both inflammatory activity and joint damage (30). With increasing disease duration, however, there is a link between joint damage and functional disability (31). Therefore, we cannot exclude that in the patients in the present study, obesity, which was associated with a higher HAQ score, was associated with increased joint destruction.…”
Section: Discussioncontrasting
confidence: 48%
“…We have observed the same phenomenon in individuals in our cohort, but due to the original SHS methodology, this cannot be seen in the data. Several studies have shown a strong relationship between progression of radiographic damage and functional disability at the end of the followup period (3,31,32). Radiographic damage, which already occurs early in the course of RA, accounts for a substantial proportion of the disability in established RA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in RA, predominantly involving white Eu-ropeans and some Northern Americans, have confirmed the important contribution of disease activity, duration, seropositivity, and the presence of radiographic damage (erosions) to disability (13)(14)(15)(16). In similar populations, the presence of secondary fibromyalgia averages 15% and may inflate self-reported disability (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%